Validation of the Arabic linguistic version of the Danish Prostatic Symptom Score for benign prostatic hyperplasia associated with lower urinary tract symptoms. Issue 4 (2nd October 2021) - Hashem, Abdelwahab; Laymon, Mahmoud; Taha, Mohamed T.; Elshabrawy, Magdy; Ghorab, Mohamed M.; Elshal, Ahmed M.; Sheir, Khaled Z.
ABSTRACT: Objective : To validate an Arabic version of the Danish Prostatic Symptom Score (DAN-PSS), a self-administered quality-of-life questionnaire. Patients and methods : The reliability of the Arabic DAN-PSS was assessed by determining the internal consistency (Cronbach's α coefficient) and by assessing the test–retest reliability (Kappa [κ] test). Inter-domain associations were examined using Spearman's correlation coefficient ( r ). The discrimination validity was evaluated using receiver operating characteristic (ROC) curves. The sensitivity to change of the questionnaire and its individual items was assessed before and after intervention using a paired t -test. Results : In all, 106 men (55 patients with BPH and 51 without BPH symptoms) were included. A high level of internal consistency amongst the three domains of the answered Arabic DAN-PSS questionnaire was observed (Cronbach's α > 0.70). Also, there was a good correlation between storage and voiding ( r = 0.75; P < 0.001) and post-micturition symptoms domains ( r = 0.51; P < 0.001). Voiding and post-micturition symptoms domains also had a good correlation ( r = 0.51; P < 0.001). The agreement between the test and retest scores had a κ value of 0.83 ( P < 0.001). The ROC curve had an area under the curve of 0.98. The sensitivity to change comparing patients with BPH who received medical or surgical intervention revealed Arabic DAN-PSS mean (SD) scores of 34.7 (17.7) and 17 (8.7) before and after the intervention, respectively ( P < 0.001). Conclusion : The Arabic DAN-PSS is a clear questionnaire, valid, reliable, and responsive that can be used for BPH associated with lower urinary tract symptoms assessment and follow-up in clinical practice and research in Arabic-speaking patients. Abbreviations : AUC: area under the curve; BPH: benign prostatic hyperplasia; CI: confidence interval; DAN-PSS: Danish Prostatic Symptom Score; DRE: digital rectal examination; ICIQ-MLUTS: International Consultation on Incontinence Male LUTS Questionnaire; ICS: international continence society; IPSS: international Prostatic Symptom Score; IPSS-Arb: Arabic version of the IPSS; LUTS: lower urinary tract symptoms; PSA: prostatic specific antigen; PSS: prostatic symptom score; QoL: quality of life; ROC: receiver operating characteristic; UTI: urinary tract infection.